Maintaining Moderate Islam in West Java: The Perspectives of Five Islam Mass Organizations Concerning Intolerance Cases - Hernawan, Wawan; Rostandi, Usep Dedi; Komarudin, Didin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This study discusses moderate Islam in West Java based on the perspectives of five mainstream Islam mass organizations: Nahdlatul Ulama, Muhammadiyah, Persatuan Umat Islam, Persatuan Islam, and Jami’atul Washliyah, concerning intolerance cases in the province in recent years. These five Islam mass organizations have roles in West Java and their perspectives are also necessarily needed to consider especially in the middle of radical-liberal, secular-fundamental streams. The study employs the Quintan Wiktorowicz socio-religious research methodology through documentation, observation, and interview techniques. The results show that the cases of intolerance in West Java have not yet resolved. There are internal, cross- and inter-religious factors both to promote and to inhibit this issue. Therefore, maintaining and giving space to the moderate Islam mass organization is suggested, as a frame in forming the behavior and religious pattern in the community.